Determinants of Phagosomal pH During Host-Pathogen Interactions - Westman, Johannes; Grinstein, Sergio (Frontiers in Cell and Developmental Biology, 2021)
The ability of phagosomes to halt microbial growth is intimately linked to their ability to acidify their luminal pH. Establishment and maintenance of an acidic lumen requires precise co-ordination of H+ pumping and counter-ion permeation to offset the countervailing H+ leakage. Despite the best efforts of professional phagocytes, however, a number of specialized pathogens survive and even replicate inside phagosomes. In such instances, pathogens target the pH-regulatory machinery of the host cell in an effort to survive inside or escape from phagosomes. This review aims to describe how phagosomal pH is regulated during phagocytosis, why it varies in different types of professional phagocytes and the strategies developed by prototypical intracellular pathogens to manipulate phagosomal pH to survive, replicate, and eventually escape from the phagocyte.